Ultrafast epitaxial growth of CuO nanowires using atmospheric pressure plasma with enhanced electrocatalytic and photocatalytic activities. Issue 3 (27th July 2021) - Dey, Avishek; Ghosh, Paheli; Chandrabose, Gauthaman; Damptey, Lois A. O.; Kuganathan, Navaratnarajah; Sainio, Sami; Nordlund, Dennis; Selvaraj, Vimalnath; Chroneos, Alexander; St J. Braithwaite, Nicholas; Krishnamurthy, Satheesh
Abstract: This work reports an environment friendly alternative to epitaxially grow copper oxide nanowires (NWs) on copper substrates using single step atmospheric pressure plasma jet assisted oxidation. NWs of average length 300 nm are grown rapidly in 5 minutes along with transforming the surface to superhydrophilic. This method introduces defects in the nanowire structure which is otherwise difficult to achieve due to the highly isotropic nature of nanowire growth. High resolution transmission electron microscopy reveals vacancies and structural defects such as lattice twinning and kinks. Theoretical investigations using density functional theory calculations indicated that oxygen vacancies reduces the adsorption energy of methanol molecules onto the CuO (111) surface and shifts the Fermi level towards conduction band. During electrocatalysis, these defect‐rich nanowires exhibit twice the catalytic activity toward oxygen evolution reaction (OER) and methanol oxidation reaction (MOR) in comparison to the traditionally thermally grown nanowires. Moreover, retreating the electrodes after each stability test drops the contact resistance similar to the prisitine sample. Additionally, these NW photocathodes demonstrate an exceptional photocurrent of 2.2 mAcm –2 and have an excellent degradation activity towards organic pollutants namely phenol and paracetamol. This facile growth method can be used to engineer nanowires of other transition metals with enhanced activities. Abstract : This work demonstrates a low cost and environment friendly route to grow and surface engineer copper oxide nanowires for enhanced electrocatalytic and photocatalytic activities.